Tokenizacija ekonomskih pravic, vezanih na nepremičnine - Merc, Peter (Pravnik, 2025)
Tokenisation is the process of issuing transferable digital tokens to which the issuer attaches rights linked to real-world assets. These tokens are issued using blockchain technology. A token represents the holder’s enforceable right to the underlying asset. In the tokenisation model described in the paper, token holders do not have an ownership right in the real estate; instead, they have a contractually guaranteed entitlement to economic rights. An example of such a right is the right to a share of the income generated by the tokenised property - for instance, rent in the case of short- or long-term lettings. From the perspective of token holders, the greatest risk is the so-called double spending by the property owner, where the owner sells the property after having tokenised the economic rights, without arranging for the transfer of the obligations arising from the tokens to the new owner of the property. This risk is mitigated by a mortgage over the property, which is one of the key instruments of the tokenisation model described. The paper addresses three research questions: (1) whether the described tokenisation model creates a minimal regulatory burden for all stakeholders, (2) whether the tokens qualify as financial instruments under MiFID-2 or as crypto-assets under MiCA, and (3) if they are classified as crypto-assets, within which category of crypto-assets such tokens fall. The tokenisation model described in this paper was first implemented in Slovenia in 2024. Tokenisation of economic rights in real estate brings several benefits for all stakeholders. The fragmentation of economic rights without a change of ownership of the property allows for greater accessibility (democratisation) of real-estate investment. From an illiquid asset such as a real estate investment, tokenisation creates a new asset class which, assuming the existence of a secondary market, is significantly more liquid. Blockchain technology, by its very design, enables greater transparency and traceability of rights and the automation of payouts and contractual terms (smart contracts).
Keywords: economic rights; ekonomske pravice; kriptosredstva; Markets in Crypto-assets Regulation; MiCA; nepremičnine; pametna pogodba; real estate; smart contract; tokenisation; tokenizacija; Uredba EU o trgih kriptosredstev (MiCA)